The genome sequence of the snout, Hypena proboscidalis (Linnaeus, 1758) - Boyes, D; Holland, PWH (F1000Research, 2021)
We present a genome assembly from an individual female Hypena proboscidalis (the snout; Arthropoda; Insecta; Lepidoptera; Erebidae). The genome sequence is 637 megabases in span. The majority of the assembly is scaffolded into 31 chromosomal pseudomolecules, with the Z sex chromosome assembled.